2015
DOI: 10.1038/pr.2015.78
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of phytosterol metabolism in neonates receiving parenteral nutrition

Abstract: BackgroundPhytosterols in soybean oil (SO) lipids likely contribute to parenteral nutrition-associated liver disease (PNALD) in infants. No characterization of phytosterol metabolism has been done in infants receiving SO lipids.MethodsIn a prospective cohort study, 45 neonates (36 SO lipid vs 9 control) underwent serial blood sample measurements of sitosterol, campesterol, and stigmasterol. Mathematical modeling was used to determine pharmacokinetic parameters of phytosterol metabolism and phytosterol exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 40 publications
(44 reference statements)
4
26
0
Order By: Relevance
“…In our PNAC infants, plasma phytosterol concentrations on both PN d7 and d14 were up to twofold higher than CTRL, and, as reported in the literature, slightly higher than those in patients with heterozygous phytosterolemia (Clayton et al, 1993;Ellegard et al, 2005;Nghiem-Rao et al, 2015;Pianese et al, 2008;Pupillo et al, 2016;Savini et al, 2013;Wang et al, 2015). The high phytosterol concentrations observed in Fig.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In our PNAC infants, plasma phytosterol concentrations on both PN d7 and d14 were up to twofold higher than CTRL, and, as reported in the literature, slightly higher than those in patients with heterozygous phytosterolemia (Clayton et al, 1993;Ellegard et al, 2005;Nghiem-Rao et al, 2015;Pianese et al, 2008;Pupillo et al, 2016;Savini et al, 2013;Wang et al, 2015). The high phytosterol concentrations observed in Fig.…”
Section: Discussionsupporting
confidence: 78%
“…In our PNAC infants, plasma phytosterol concentrations on both PN d7 and d14 were up to twofold higher than CTRL, and, as reported in the literature, slightly higher than those in patients with heterozygous phytosterolemia (Clayton et al, ; Ellegard et al, ; Nghiem‐Rao et al, ; Pianese et al, ; Pupillo et al, ; Savini et al, ; Wang et al, ). The high phytosterol concentrations observed in PNAC infants suggest that they may have poorly developed mechanisms of metabolizing phytosterols and that there might be a link between phytosterols and cholestasis (Bindl et al, ; Iyer et al, ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In a prospective study of 45 infants, we found that infants who received a short duration of soy oil–based IVFEs had significantly higher levels of sitosterol and campesterol versus control infants who did not receive soy oil–based IVFE. In those who received soy oil–based IVFE, very preterm infants born <28 weeks of gestational age had a significantly higher steady state level and area under the curve for sitosterol as compared with more mature infants 54 . These findings indicate that very preterm infants accumulate more sitosterol than more mature infants, suggesting a developmental inability to regulate sterol levels that may contribute to the increased vulnerability of preterm infants to IFALD.…”
Section: Toxic Components Of Soy‐based Ivfementioning
confidence: 89%
“…These results could be explained by the different effect of phytosterol structure upon LCAT and ACAT activity resulting in different esterification rates. However, a faster incorporation of Ester-PHY into membranes cannot be excluded, even if all study patients received IV lipids for a quite long period of time before sampling and, thus, were likely at a steady state [30]. In vitro reconstitution of sterol transfer by G5 and G8 in a cell-free system showed a better sterol-free ABCG5/ABCG8-mediated transport than that of esterified sterols [31].…”
Section: Discussionmentioning
confidence: 99%